2018
DOI: 10.1111/adb.12611
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of Dopamine β‐Hydroxylase in cocaine dependence therapy with doxazosin

Abstract: The α -adrenergic antagonist, doxazosin, has improved cocaine use disorder (CUD) presumably by blocking norepinephrine (NE) stimulation and reward from cocaine-induced NE increases. If the NE levels for release were lower, then doxazosin might more readily block this NE stimulation and be more effective. The NE available for release can be lower through a genetic polymorphism in dopamine β-hydroxylase (DBH) (C-1021T, rs1611115), which reduces DβH's conversion of dopamine to NE. We hypothesize that doxazosin wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Early CUD pharmacogenetic studies focused on mouse models (reviewed by [131]). Now, some double-blind randomized placebo-control trials in humans have been performed to analyze cocaine drug treatment response based on the genotypes of specific functional variants on ten genes (ADRA1A, ADRA1D, ANKK1, DRD2, DBH, MTHFR, OPRK1, THP2, SLC6A4, and SLC6A3) related with cocaine physiological mechanisms [132][133][134][135][136][137][138][139][140][141][142][143]. The medications assessed include doxazosin, an α1A adrenergic antagonist that decreases noradrenergic activity; levodopa, a dopamine precursor; cocaine vaccine, succinylnorcocaine covalently linked to cholera B [137]; and disulfiram, a cooper chelator that inhibits noradrenergic synthesis.…”
Section: Treatment and Pharmacogeneticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Early CUD pharmacogenetic studies focused on mouse models (reviewed by [131]). Now, some double-blind randomized placebo-control trials in humans have been performed to analyze cocaine drug treatment response based on the genotypes of specific functional variants on ten genes (ADRA1A, ADRA1D, ANKK1, DRD2, DBH, MTHFR, OPRK1, THP2, SLC6A4, and SLC6A3) related with cocaine physiological mechanisms [132][133][134][135][136][137][138][139][140][141][142][143]. The medications assessed include doxazosin, an α1A adrenergic antagonist that decreases noradrenergic activity; levodopa, a dopamine precursor; cocaine vaccine, succinylnorcocaine covalently linked to cholera B [137]; and disulfiram, a cooper chelator that inhibits noradrenergic synthesis.…”
Section: Treatment and Pharmacogeneticsmentioning
confidence: 99%
“…Interestingly, the SNP rs161115 (-1021C>T) in the dopamine βhydroxylase gene (DBH), responsible for up to 50% of plasma activity variation of the enzyme, has been analyzed in multiple studies. Different clinical responses for each allele (C/T) were observed when distinct treatments were used [134][135][136][137][138], suggesting that the individual's genotype could help to make treatment choices. For instance, individuals with the CC genotype, associated with normal DBH levels, presented significant cocaine-positive urine reduction rates on disulfiram treatment in one study [136], although the results were not supported by another study [135].…”
Section: Treatment and Pharmacogeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both family history and BP are being measured in the current study. Future research in this area should include measurements of pre-treatment BP, family history of AUD, as well as genetic data [75]. …”
Section: Discussionmentioning
confidence: 99%
“…In a recent trial, doxazosin‐treated (8 mg/day) individuals exhibited a greater reduction in cocaine use relative to those treated with placebo [45]. Genetic subgroup analysis further indicated that the percentage of cocaine‐positive urine toxicology screens for doxazosin‐treated individuals was lower in the group with lower DA beta‐hydroxylase (DβH) levels from T‐allele carriers (CT or TT) than the group with higher DβH levels from the DβH CC genotype.…”
Section: Current Approaches To Treating Cudmentioning
confidence: 99%